Análise de atividade esquistossomicida da 7-epiclusianona utilizando ferramentas bioquímicas e moleculares - Silva, Matheus Siqueira (2016)
Schistosomiasis is a neglected tropical disease with high morbidity and mortality, which currently affects more than 200 million people worldwide, counting only with praziquantel (PZQ) as a treatment option. Studies describe various parasite strains that are resistant to PZQ, making it necessary, studies of new drugs that can be used to treat schistosomiasis. One of the principles of drugs rational planning is to choose targets where the drug produces selective toxic effects on the pathogen, and for this is necessary to define the action mechanism of the proposed pharmaco. 7-epiclusianone (7-epi) already has schistosomicidal activity described, using as criteria of effectiveness: the motility, integument damage, mating, egg-laying and motility of the digestive and excretory system. In this direction, the present study analyzed the impact of the 7-epi against the protective mechanisms of adult worms of S. mansoni with the support of biochemical and biomolecular tools. An investigation of the degree of oxidative stress by malondialdehyde titre showed that the 7-epi at a concentration of 12,5 μg/mL has lower levels of lipid peroxidation rate comparing to the Kolliphor® control, but increased in concentration of 50 μg/ml (p <0,001). Similarly, when it investigated the activity of superoxide dismutase (SOD), an important parasite detox enzyme, in ex vivo context it was possible to see the 7-epi interfere in its activity significantly, compared to controls RPMI-1640 and Kolliphor® at a concentration of 12,5 μg /mL (p <0,001). This value corresponds to 30% of the entire enzyme activity regarding Kolliphor® and is close to the effective dose that killed 90% of the parasites (ED90=13,08 μg/mL) in which integument damages were intense. In addition, the analysis by molecular docking can observe that the inhibition of the enzyme was not performed directly on site, and that the best interaction energies with 7-epi were in a cavity near the site and in the dimer’s junction. Finally, quantitative analyzes were made by qPCR of mRNA from SOD of the parasite, that results showed no significant change in enzyme transcription after the 7-epi action. Although there is an impact on the activity of SOD of S. mansoni, this does not seem to be 7-epi main mechanism of action. Thus, it is essential the inhibitory evaluation of this compound in other parasite enzymes as well as the analysis of other non-enzymatic mechanisms that elucidate the action of 7-epi in adult worms of S. mansoni.